P349 Safety of Inflammatory Bowel Disease treatments in patients with Solid Organ Transplantation (EITOS study of GETECCU). (21st January 2022) - Bastón Rey, I; Calvino Suárez, C; Luque, A M; Caballol, B; Soutullo, C; Bravo, A; Castaño, A; Gros, B; Hurtado, A; Vázquez Rey, T; Alonso Galán, H; Cañete, F; et al.
Abstract: Background: Inflammatory bowel disease (IBD) in patients with solid organ transplantation (SOT) is associated with a greater complexity in their medical management. The aim of this study was to evaluate the safety profile of different IBD treatments in patients with IBD and SOT. Methods: A retrospective, observational multi-center study was designed. IBD patients with SOT were included in two separate cohorts: (1) patients with pre-existing IBD and (2) patients without IBD at the time of SOT (de novo IBD). The primary outcome was to evaluate the presence of severe infections (opportunistic infections or infection that required hospitalization) and malignancies. Predictive factors for infections were identified by logistic regression. Results: A total of, 177 patients (106 pre-existing IBD and, 71 de novo IBD) from, 31 centers were included. Baseline characteristics are shown in Table, 1. Tacrolimus was the most commonly used antirejection treatment (153 patients, 88.7%). In the pre-existing IBD cohort, after SOT, 61 patients (59.8%) were not under treatment or were treated with, 5-aminosalicylates, 10 patients (9.8%) were on azathioprine and, 31 (30.4%) were on biologics, of which, 8 were on combo therapy. In the pre-existing IBD cohort, 47.1% patients had severe infections being cytomegalovirus (CMV) infection, acute cholangitis and Clostridioides difficile (C.Diff) colitis the most common (Fig. 1). In de novo IBD cohort, 13 patients (18.3%) were on azathioprine and, 28 (39.4%) were on biologics, of which, 4 were on combo therapy. Half of patients in de novo IBD cohort (54.9%) had severe infections, being CMV infection and pneumonia the most frequently observed. C.Diff colitis was less frequent in this group (Fig 2). Asystole donor (OR, 3.7, 95%CI, 1.1–12.6), primary sclerosing cholangitis (PSC) (OR, 3.3, 95%CI, 1.3–8.6) and retransplantation (OR, 10.8, 95%CI, 1.2–98.8) were identified as risk factors for severe infection after SOT in patients with pre-existing IBD. No treatment was significantly associated with increased risk of infections. In the pre-existing IBD cohort, 14 (13.5%) developed at least one malignancy after SOT over a median of, 5 years (range, 1.2–10.1). In patients with de novo IBD, 13 (18.3%) developed cancer after the diagnosis of IBD over a median of, 6.6 years (range, 2.9–8.0). Non-melanoma skin cancer was the most frequent malignancy in both groups. Two colorectal cancers were detected in each cohort. Conclusion: About half of patients with IBD and SOT develop severe infections, being CMV the most frequent involved. Asystole donor, PSC and retransplantation are associated with increased risk of infection after SOT in pre-existing IBD cohort. Both groups show an elevated incidence of malignancies, being non-melanoma skin cancer the most common.